2002
DOI: 10.1128/jcm.40.9.3364-3373.2002
|View full text |Cite
|
Sign up to set email alerts
|

Rapid-Cycle PCR and Fluorimetry for Detection of Mycobacteria

Abstract: In this study we used LightCycler PCR amplification and product detection by fluorescence resonance energy transfer probes to identify mycobacteria and differentiate between Mycobacterium tuberculosis complex, Mycobacterium avium, and other nontuberculous mycobacteria. Targeting the 16S rRNA gene, three different probes specific for mycobacteria, M. tuberculosis complex, and M. avium were constructed. As few as five genome copies of target nucleic acid were detected by the probes, illustrating the high sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
63
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 26 publications
0
63
0
Order By: Relevance
“…For example, dual-hybridization probes have been used to detect 33 species of mycobacteria using the 16S rRNA gene. 75 LightCycler technology has been applied to many bacteria, fungi, and parasites. Targeting a single pathogen of clinical importance can immediately guide therapy.…”
Section: Microbiologymentioning
confidence: 99%
“…For example, dual-hybridization probes have been used to detect 33 species of mycobacteria using the 16S rRNA gene. 75 LightCycler technology has been applied to many bacteria, fungi, and parasites. Targeting a single pathogen of clinical importance can immediately guide therapy.…”
Section: Microbiologymentioning
confidence: 99%
“…Many regions of the mycobacterial genome have been used in molecular diagnosis of TB, such as IS6110, 16S rRNA, hsp65, rpoB, sdaA, devR and mpt64 (Manjunath et al, 1991;Lachnik et al, 2002;Kim et al, 2004;Chakravorty et al, 2005;Negi et al, 2007;Hwang et al, 2013;Nimesh et al, 2013). mpt64 is found as a single copy in the genome of MTBC species (Lee et al, 1994), and has been used for both pulmonary and extrapulmonary TB diagnosis (Tan et al, 1995;Dar et al, 1998;Martins et al, 2000;Bhanu et al, 2005;Therese et al, 2005;Takahashi & Nakayama, 2006;Dil-Afroze et al, 2008;Kusum et al, 2012;Sethi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Building on this work, many groups have shown that drug response is also influenced by genomic variation (6 ). Multiple SNPs have been identified that have a major impact on response to chemotherapy (7)(8)(9)(10)(11); it is therefore necessary to have rapid and efficient SNP evaluation techniques to analyze genes that influence chemotherapy response.…”
mentioning
confidence: 99%